SPEAKING PROBLEMS FACED BY THE SECONDARY SCHOOL PUPILS: SPEAKING PROBLEMS FACED BY THE SECONDARY SCHOOL PUPILS - Urazmatova, Manzura (Журнал иностранных языков и лингвистики, 2025)
Learning foreign languages is considered as one of the most challenging phenomenon. Therefore, numerous pupils mainly encounter obstacles in their oral speech. These difficulties may occur because of vocabulary hurdles, linguistic complexity, flawed strategies, poor pronunciation, less practice or fear of expressing their ideas. This study has indicated the main problems during speaking process and has given appropriate methods as a solution.